(Dys)functional cognitive-behavioral coping strategies of teachers to cope with stress, anxiety, and depression - Ghasemi, Farshad (Deviant behavior, 2022)
The prevalence of teacher stress, anxiety, and depression (SAD) has been confirmed and investigated in various contexts. This research aimed to study the (dys)functional coping strategies (CSs) of teachers and their experienced SAD levels. Of the 549 invited language teachers, 398 (75%) teachers with various occupational attributes participated in this study by completing the (Dys)functional Coping Strategies Scales (DCSS) and the Depression, Anxiety, and Stress Scales (DASS). The results indicated high teacher SAD rates (M = 31%). Regarding teacher professional characteristics, preservice teachers were more susceptible to suffer from stress, while expert teachers were at risk of experiencing anxiety and depression. Among the recognized functional CSs, talking with friends, parents, etc. and self-monitoring to control feelings appear to be the two important protective cognitive-behavioral (C-B) mechanisms to deal with teacher SAD. Using negative self-talk and self-blame and smoking cigarettes (excessively) were the concerning coping mechanisms of teachers with SAD. It is suggested that effective and continuous interventions should be developed and incorporated into teacher education programs to equip teachers with required CSs and to promote functional C-B conducts and strategies.